Microbial ecology of arsenic‐mobilizing Cambodian sediments: lithological controls uncovered by stable‐isotope probing. (5th March 2014) - Héry, Marina; Rizoulis, Athanasios; Sanguin, Hervé; Cooke, David A.; Pancost, Richard D.; Polya, David A.; Lloyd, Jonathan R.
Summary Microbially mediated arsenic release from Holocene and Pleistocene Cambodian aquifer sediments was investigated using microcosm experiments and substrate amendments. In the Holocene sediment, the metabolically active bacteria, including arsenate‐respiring bacteria, were determined by DNA stable‐isotope probing. After incubation with 13C‐acetate and 13C‐lactate, active bacterial community in the Holocene sediment was dominated by different Geobacter spp.‐related 16S rRNA sequences. Substrate addition also resulted in the enrichment of sequences related to the arsenate‐respiring Sulfurospirillum spp. 13C‐acetate selected for ArrA related to Geobacter spp. whereas 13C‐lactate selected for ArrA which were not closely related to any cultivated organism. Incubation of the Pleistocene sediment with lactate favoured a 16S rRNA‐phylotype related to the sulphate‐reducing Desulfovibrio oxamicus DSM1925, whereas the ArrA sequences clustered with environmental sequences distinct from those identified in the Holocene sediment. Whereas limited As(III) release was observed in Pleistocene sediment after lactate addition, no arsenic mobilization occurred from Holocene sediments, probably because of the initial reduced state of As, as determined by X‐ray Absorption Near Edge Structure. Our findings demonstrate that in the presence of reactive organic carbon, As(III) mobilization can occur in Pleistocene sediments, having implications for future strategies that aim to reduce arsenic contamination in drinking waters by using aquifers containing Pleistocene sediments.